Evaluating the NASA MPLNET Rain Masking Algorithm at Goddard Space Flight Center and Barcelona sites: Relevance to EarthCARE Cloud Profiling Radar Validation - Simone Lolli; Jasper R. Lewis; Ali Tokay; Gemine Vivone; James R. Campbell; Erica K. Dolinar; Michael Sïcard; Adolfo Comerón; Alejandro Rodriguez-Gomez; Constantino Muñoz-Porcar; Albert García-Benadí; Mireia Udina; et al. (Atmospheric Research, 2026)

Evaluation of the geochemical background of soil in a hyper-arid zone using a multivariate statistical methodology: The case of the city of Antofagasta in the Atacama Desert - Brian F. Keith; Elizabeth J. Lam; Ítalo L. Montofré; Vicente Zetola; Javier Urrutia; Christian Herrera; Jaume Bech (Chemosphere, 2024)

Potentially harmful elements pollute soil and vegetation around the Atrevida mine (Tarragona, NE Spain) - L. Roca-Perez; R. Boluda; J. A. Rodríguez-Martín; J. Ramos-Miras; P. Tume; N. Roca; J. Bech (Environmental Geochemistry and Health, 2023)
Mining activity is one of the main sources to pollute soil, water and plants. An analysis of soil and plant samples around the Atrevida mining area in Catalonia (NE Spain) was preformed to determine potentially harmful elements (PHEs). Soil and plant samples were taken at eight locations around the mining area. The topsoil (0–15 cm) samples were analysed for physico-chemical properties by standard methods, by ICP-MS for Cd, Co, Cr, Cu, Fe, Ni, Pb and Zn, and were microwave-digested. Plant, root and shoot samples were digested separately, and heavy metals were analysed by AAS. Translocation factor (TF), biological concentration factor (BCF) and biological accumulation factor (BAF) were determined to assess the tolerance strategies developed by native species and to evaluate their potential for phytoremediation purposes. Soil pH was generally acid (5.48–6.72), with high soil organic matter (SOM) content and a sandy loamy or loamy texture. According to the agricultural soil values in southern Europe, our PHEs concentrations exceeded the toxicity thresholds. The highest root content of the most studied PHEs appeared in Thymus vulgaris L. and Festuca ovina L., while Biscutella laevigata L. accumulated more PHEs in shoots. The TF values were > 1 in B. laevigata L., but BAF obtained < 1, except Pb. B. laevigata L., and can be considered potentially useful for phytoremediation for having the capacity to restrict the accumulation of large PHEs amounts in roots and Pb translocation to shoots.

An extension of the characteristic curve model of plant species behavior in heavy metal soils - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; María E. Gálvez; Rodrigo Rojas; Fernando A. Alvarez; Vicente Zetola; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

The dynamics of boron when amending agricultural soil of the Mediterranean basin with biosolids: trials in leaching columns - M. M. Jordán; M. B. Almendro-Candel; J. Navarro-Pedreño; E. García-Sánchez; F. Pardo; J. Bech (Environmental Geochemistry and Health, 2023)

Characteristic curve modeling of plant species behavior in soils with heavy metals - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; Fernando A. Alvarez; Vicente Zetola; Luis H. Pereira; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

Targeted hydrolysis of native potato protein: A novel workflow for obtaining hydrolysates with improved interfacial properties - Simon Gregersen Echers; Ali Jafarpour; Betül Yesiltas; Pedro J. García-Moreno; Mathias Greve-Poulsen; Dennis K. Hansen; Charlotte Jacobsen; Michael Toft Overgaard; Egon Bech Hansen (Food Hydrocolloids, 2023)

Heavy metal pollution index calculation in geochemistry assessment: a case study on Playa Las Petroleras - Elizabeth J. Lam; Javier Urrutia; Jaume Bech; Christian Herrera; Ítalo L. Montofré; Vicente Zetola; Fernando A. Álvarez; Manuel Cánovas (Environmental Geochemistry and Health, 2023)

Extent of introgressive hybridization in the Hermann’s tortoise (Testudo hermanni hermanni) from the south of France - N. Bech; D. Nivelle; S. Caron; J. M. Ballouard; V. Arnal; D. Arsovski; A. Golubović; X. Bonnet; C. Montgelard (European Journal of Wildlife Research, 2022)

Bioavailability, mobility and leaching of phosphorus in a Mediterranean agricultural soil (ne Spain) amended with different doses of biosolids - M. M. Jordán; M. B. Almendro-Candel; J. Navarro-Pedreño; F. Pardo; E. García-Sánchez; J. Bech (Environmental Geochemistry and Health, 2022)

Urban areas, human health and technosols for the green deal - T. Rodríguez-Espinosa; J. Navarro-Pedreño; I. Gómez-Lucas; M. M. Jordán-Vidal; J. Bech-Borras; A. A. Zorpas (Environmental Geochemistry and Health, 2021)

Observed Changes in Daily Precipitation Extremes at Annual Timescale Over the Eastern Mediterranean During 1961–2012 - S. Mathbout; J. A. Lopez-Bustins; D. Royé; J. Martin-Vide; J. Bech; F. S. Rodrigo (Pure and Applied Geophysics, 2018)

Polymeric nanocapsules: a potential new therapy for corneal wound healing - Sonia Reimondez-Troitiño; Ignacio Alcalde; Noemi Csaba; Almudena Íñigo-Portugués; María de la Fuente; Federico Bech; Ana C. Riestra; Jesús Merayo-Lloves; María J. Alonso (Drug Delivery and Translational Research, 2016)

Genetic footprints reveal geographic patterns of expansion in Fennoscandian red foxes - Karin Norén; Mark J. Statham; Erik O. Ågren; Marja Isomursu; Øystein Flagstad; Nina E. Eide; Thomas Bjørneboe G. Berg; Lene Bech‐Sanderhoff; Benjamin N. Sacks (Global Change Biology, 2015)
Population expansions of boreal species are among the most substantial ecological consequences of climate change, potentially transforming both structure and processes of northern ecosystems. Despite their importance, little is known about expansion dynamics of boreal species. Red foxes ( Vulpes vulpes ) are forecasted to become a keystone species in northern Europe, a process stemming from population expansions that began in the 19th century. To identify the relative roles of geographic and demographic factors and the sources of northern European red fox population expansion, we genotyped 21 microsatellite loci in modern and historical (1835–1941) Fennoscandian red foxes. Using Bayesian clustering and Bayesian inference of migration rates, we identified high connectivity and asymmetric migration rates across the region, consistent with source‐sink dynamics, whereby more recently colonized sampling regions received immigrants from multiple sources. There were no clear clines in allele frequency or genetic diversity as would be expected from a unidirectional range expansion from south to north. Instead, migration inferences, demographic models and comparison to historical red fox genotypes suggested that the population expansion of the red fox is a consequence of dispersal from multiple sources, as well as in situ demographic growth. Together, these findings provide a rare glimpse into the anatomy of a boreal range expansion and enable informed predictions about future changes in boreal communities.

Analysis of 14 years of broadband ground‐based solar UV index observations in Barcelona - J. Bech; Y. Sola; A. Ossó; J. Lorente (International Journal of Climatology, 2015)
This study presents an analysis of a 14‐year data set of 30‐min averaged experimental UVI values derived from ground‐based broadband irradiance measurements, satellite‐derived total ozone observations and total solar radiation recorded in Barcelona ( NE Spain). Most maximum daily UVI values do occur at noon (82% of cases between 11:30 and 13:00 UTC ). Considering all seasons, the maximum daily UVI presents a bimodal, approximately symmetrical, frequency distribution with a maximum around UVI class 2 (22%) and UVI 7 and 8 classes (23%) while June median presents a value of 8.2. According to attenuation criteria there is a preponderance of Clear sky days (77%) compared to Broken (22%) and Overcast (8%) conditions, which concentrate mostly in October, November and December (reaching 20% of days). An additional classification in terms of World Health Organisation UVI intensity categories indicates that 40% of days exceeded the Lower threshold of UVI category Moderate ( UVI values above 5.5), from them 21% of days had UVI values considered Very High (above 9.5) and one single case was classified as Extreme ( UVI above 10.5). UVI values above 7.5 were found under Broken sky conditions in June, July and August. Additionally UVI diurnal daily cycles have also been analyzed in terms of selected percentile values and maximum levels. Under all sky conditions UVI median values exceed the lower threshold of category High (5.5) from April to late August around noon (in June from 10:00 to 14:30 UTC ). These results provide an exhaustive quantitative description of average and extreme values of experimental UVI values observed in the region and can be of interest for a wide range of applications, including ground‐based UV modelling through the use of radiative transfer models, trend analysis or verification of UVI forecasts.

Host tissues as microhabitats for W olbachia and quantitative insights into the bacterial community in terrestrial isopods - J. Dittmer; S. Beltran‐Bech; J. Lesobre; M. Raimond; M. Johnson; D. Bouchon (Molecular Ecology, 2014)
Animal–bacterial symbioses are highly dynamic in terms of multipartite interactions, both between the host and its symbionts as well as between the different bacteria constituting the symbiotic community. These interactions will be reflected by the titres of the individual bacterial taxa, for example via host regulation of bacterial loads or competition for resources between symbionts. Moreover, different host tissues represent heterogeneous microhabitats for bacteria, meaning that host‐associated bacteria might establish tissue‐specific bacterial communities. W olbachia are widespread endosymbiotic bacteria, infecting a large number of arthropods and filarial nematodes. However, relatively little is known regarding direct interactions between W olbachia and other bacteria. This study represents the first quantitative investigation of tissue‐specific W olbachia –microbiota interactions in the terrestrial isopod A rmadillidium vulgare . To this end, we obtained a more complete picture of the W olbachia distribution patterns across all major host tissues, integrating all three feminizing W olbachia strains ( w VulM, w VulC, w VulP) identified to date in this host. Interestingly, the different W olbachia strains exhibited strain‐specific tissue distribution patterns, with w VulM reaching lower titres in most tissues. These patterns were consistent across different host genetic backgrounds and might reflect different co‐evolutionary histories between the W olbachia strains and A . vulgare . Moreover, W olbachia ‐infected females carried higher total bacterial loads in several, but not all, tissues, irrespective of the W olbachia strain. Taken together, this quantitative approach indicates that W olbachia is part of a potentially more diverse bacterial community, as exemplified by the presence of highly abundant bacterial taxa in the midgut caeca of several A . vulgare populations.

Forecasting weather radar propagation conditions - J. Bech; B. Codina; J. Lorente (Meteorology and Atmospheric Physics, 2007)

ADAMs, cell migration and cancer - Joaquín Arribas; Joan J. Bech-Serra; Belén Santiago-Josefat (Cancer and Metastasis Reviews, 2006)

A comparison of the effects of etodolac and ibuprofen on renal haemodynamics, tubular function, renin, vasopressin and urinary excretion of albumin and α-glutathione- S -transferase in healthy subjects: a placebo-controlled cross-over study - K. B. Svendsen; J. N. Bech; T. B. Sørensen; E. B. Pedersen (European Journal of Clinical Pharmacology, 2000)

Assessment of the Heavy Metal Pollution Effects on the Soil Respiration in the Baix Llobregat (Catalonia, NE Spain) - Danuta Zimakowska-Gnoińska; Jaume Bech; Francisco J. Tobias (Environmental Monitoring and Assessment, 2000)

Influence of body composition on the metabolic rate of nestling European shags ( Phalacrocorax aristotelis ) - C. Bech; J. E. Østnes (Journal of Comparative Physiology B, 1999)

Yolk PCB and Plasma Retinol Concentrations in Shag ( Phalacrocorax aristotelis ) Hatchlings - K. M. Murvoll; J. U. Skaare; V. H. Nilssen; C. Bech; J. E. Østnes; B. M. Jenssen (Archives of Environmental Contamination and Toxicology, 1999)

Localization of a gene for incomplete X-linked congenital stationary night blindness to the interval between DXS6849 and DXS8023 in Xp11.23 - N. T. Bech-Hansen; Kym M. Boycott; Kathy J. Gratton; Daniel A. Ross; L. Leigh Field; William G. Pearce (Human Genetics, 1998)

Statistical Approach to Discriminate Background and Anthropogenic Input of Trace Elements in Soils of Catalonia, Spain - F. J. Tobías; J. Bech; P. Sánchez Algarra (Water, Air, & Soil Pollution, 1997)

Serotonin 1A receptor autoradiography during alcohol-withdrawal kindling - J. Ulrichsen; Bjarke Ebert; Steven Haugbøl; B. Bech; Christian Holkmann Olsen; Nils Henrik Diemer; Ralf Hemmingsen (Psychopharmacology, 1997)